E-COMMERCE TOKO NANA BERBASIS WEB MOBILE DENGAN ONGKOS KIRIM JNE (Information Technology and Telematics, 2015)
Abstract By leveraging web technology mobile online can give you a faster report rendering in the transaction which can facilitate consumers in making a booking boots and sandals or just looking at stuff and prices through the mobile web. The application to be built using mobile and web-based programming languages PHP, Mysql, Jquery Mobile Database with editor Notepad ++. This application is created by using openchart CMS and uses the jquery mobile framework as it looks and mysql as the database. These applications can be running on a mobile device browser. Web-based Online sales system Mobile is also designed using the design tool system in UML (Unified Modelling Language). UML is one of the tools in object-oriented systems development. This is because UML modeling provides a visual language that allows for system developers, as well as easy to understand and provided with an effective mechanism to share and communicate designs with the other. This research resulted in The E-commerce Store shoes and Sandals Nana Holy City Based Mobile Web features with Counters Postage JNE. E-commerce website works as a media development promotion publication information store shoes and slippers. As for suggestions that can be input are as follows: The addition of product display order can slidshow becomes more attractive, the availability of payment in the form of credit or vocher, need for applications in the form of android. Key words: store shoes and slippers, eCommerce, UML, CMS, Mobile Web